Sabrina the teenage witch millenium madness. (London : Pocket Books, 1999)
Sabrina has to go through a series of adventures leading up to Y2K.
"An Archway paperback.".
"Based on the hit TV series.".
6.5
3-6
Keywords: Millenium -- Fiction; Witches -- Fiction